2016
DOI: 10.1080/09168451.2015.1083399
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the chitin degradation and utilization system by the ChiX small RNA in Serratia marcescens 2170

Abstract: Serratia marcescens 2170 produces three different types of chitinases and chitin-binding protein CBP21. We found that transposon insertion into the 5' untranslated region (5' UTR) of chiPQ-ctb led to defective chitinase and CBP21 production. ChiX small RNA possessed the complementary sequence of the 5' UTRs of the chiPQ-ctb and chiR and repressed the expression of chiP and chiR. ChiX was detected in a medium containing glucose, glycerol, GlcNAc, and (GlcNAc)2, but the expression of both chiP and chiR was only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Expression of the four chitinases and the secretion machinery is under control of the LysR-type transcription factor ChiR (Suzuki et al, 2001;Costa et al, 2019). A further layer of regulation is mediated via small RNA encoded in the 5'-untranslated region of chiP that acts as a post-transcriptional repressor of chiR expression (Suzuki et al, 2016) (unfortunately also named chiX in the original publication but here labeled crsA for chitinase regulatory sRNA A to distinguish it from the endopeptidase ChiX). IM, inner membrane; OM, outer membrane F I G U R E 2 Subcellular location and predicted topology of components of the S. marcescens chitinase secretion system.…”
Section: Chitinase Secretion By Serratia Marcescens Db10 As a Paradmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the four chitinases and the secretion machinery is under control of the LysR-type transcription factor ChiR (Suzuki et al, 2001;Costa et al, 2019). A further layer of regulation is mediated via small RNA encoded in the 5'-untranslated region of chiP that acts as a post-transcriptional repressor of chiR expression (Suzuki et al, 2016) (unfortunately also named chiX in the original publication but here labeled crsA for chitinase regulatory sRNA A to distinguish it from the endopeptidase ChiX). IM, inner membrane; OM, outer membrane F I G U R E 2 Subcellular location and predicted topology of components of the S. marcescens chitinase secretion system.…”
Section: Chitinase Secretion By Serratia Marcescens Db10 As a Paradmentioning
confidence: 99%
“…For example, comparative analysis of the extracellular proteomes of a wild‐type and isogenic chiW mutant strain using a sensitive mass spectrometry technique identifies only a handful of proteins that decrease significantly in abundance in the absence of ChiW, and these are predominantly extracellular components of chitinolytic machinery (Hamilton et al ., 2014; Costa et al ., 2019). The S. marcescens DB10 chitinase secretion machinery is co‐ordinately regulated with the chitinase enzymes through the action of a LysR‐family transcriptional regulator, ChiR (Suzuki et al ., 2001; Suzuki et al ., 2016; Yan et al ., 2017; Costa et al ., 2019). LysR‐type regulators are generally activated though interaction with a small metabolite, although at present the co‐activator of ChiR is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ChiR was originally identified in genetic screens focused on screening for chitinase activity (7,9) and was later exploited as a positive regulator of chitinase activity in biotechnological applications (11). Regulation of chitinases is thought to be further influenced by the presence of chitobiose (the GlcNAc disaccharide) (15) and by small regulatory RNAs (16). We have no evidence here that a significant shift in bimodality would occur if a chitin source or breakdown were to be encountered by the population, but since growth on GlcNAc as sole carbon source led to 13% of cells 'ON' for GFP-ChiC production, this may be unlikely (Supp.…”
Section: Chir Controls Bimodality Of Expression Of the Chitinolytic Mmentioning
confidence: 99%
“…In particular, the ÁchiP mutant showed a significantly lower ability to grow on media supplemented with colloidal chitin and chitobiose, and showed no growth on media containing chitotriose. Subsequent studies demonstrated that the chiX small RNA controls the expression of chitin-degrading enzymes (chitinases and chitobiase), a chitinbinding protein (CBP21) and a chitooligosaccharide transporter (ChiP) (Toratani et al, 2012;Suzuki et al, 2016). Nevertheless, no detailed functional and structural characterization of chitin acquisition by SmChiP has been performed to date.…”
Section: Introductionmentioning
confidence: 99%